Promotional Effect of Tertiary Amine on Asymmetric Catalytic Hydrogenation of Ethyl Pyruvate Over Pt/Al2O3 in Acetic Acid - TAO, GUOZHONG; LU*, GUANZHONG; GUO, YUN; WANG, YANQIN; GUO, YANGLONG (Asian Journal of Chemistry, 2009)
In the asymmetric hydrogenation of ethyl pyruvate over cinchonaalkaloid modified Pt/Al2O3 in acetic acid under atmospheric pressure,the enantioselectivity was improved and the reaction rate was acceleratedupon addition of tertiary amine. The size of the alkyl substitute in tertiaryamine molecule has significant impact on the improvement. Triethylamineis the most effective additive compared with tri-n-butylamine,tri-n-propylamine and trimethylamine. There is an optimum addingamount (0.4 mol/L) of all tertiary amines, at which triethylamine canincrease the enantioselectivity of product from 51 to 72 %. The role oftertiary amine in the promotional effect was discussed.